2023
DOI: 10.3390/jpm13020225
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics in Lung Metastases: A Systematic Review

Abstract: Due to the rich vascularization and lymphatic drainage of the pulmonary tissue, lung metastases (LM) are not uncommon in patients with cancer. Radiomics is an active research field aimed at the extraction of quantitative data from diagnostic images, which can serve as useful imaging biomarkers for a more effective, personalized patient care. Our purpose is to illustrate the current applications, strengths and weaknesses of radiomics for lesion characterization, treatment planning and prognostic assessment in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 127 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, our evaluation framework using bootstrap-bias-corrected 10-times-repeated 20-fold crossvalidation accounts for the variance introduced by an arbitrary single train/test split in small sample sizes [18,27] and measures both calibration and discrimination [27]. Other authors applied radiomics to primary pulmonary neoplasms and metastases in CECT and PET/CT [28][29][30][31][32][33]. Predicted outcomes were composed of the severity of pulmonary lesions, epidermal growth factor receptor status, or survival outcomes [28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our evaluation framework using bootstrap-bias-corrected 10-times-repeated 20-fold crossvalidation accounts for the variance introduced by an arbitrary single train/test split in small sample sizes [18,27] and measures both calibration and discrimination [27]. Other authors applied radiomics to primary pulmonary neoplasms and metastases in CECT and PET/CT [28][29][30][31][32][33]. Predicted outcomes were composed of the severity of pulmonary lesions, epidermal growth factor receptor status, or survival outcomes [28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors applied radiomics to primary pulmonary neoplasms and metastases in CECT and PET/CT [28][29][30][31][32][33]. Predicted outcomes were composed of the severity of pulmonary lesions, epidermal growth factor receptor status, or survival outcomes [28][29][30][31][32][33]. In contrast, we focus on the per-node dignity of thoracic lymph nodes, where rather little research has been conducted [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that radiomics has the potential to improve or surpass existing tumor diagnosis methods, as it can effectively evaluate genomic features [24,25], tumor subtypes [26][27][28], and lymph node metastasis [29][30][31][32] in various cancers. Radiomics has demonstrated the ability to predict the prognosis of various malignancies, including colorectal cancer [33][34][35][36][37][38], gastric cancer [39][40][41][42][43][44], cervical cancer [31,[45][46][47][48], pancreatic cancer [49][50][51], nasopharyngeal cancer [52][53][54][55][56][57], breast cancer [58][59][60][61][62], and lung cancer [63][64][65][66][67][68]. To conduct a comprehensive literature review, we employed the PubMed search engine in combination with an online litera...…”
Section: Introductionmentioning
confidence: 99%
“…In particular, texture analysis (TA) has been increasingly applied to radiological imaging for diagnosing, characterizing, and monitoring treatment response by quantifying tumor heterogeneity and irregularity of tissue components [12,13]. Tumors with high heterogeneity have been shown to have worse prognosis, potentially reflecting intrinsic biological aggressiveness or treatment resistance [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%